2015
DOI: 10.1091/mbc.e14-03-0797
|View full text |Cite
|
Sign up to set email alerts
|

KIF5B transports BNIP-2 to regulate p38 mitogen-activated protein kinase activation and myoblast differentiation

Abstract: Cdo bridges scaffold proteins BNIP-2 and JLP to activate p38MAPK during myoblast differentiation. KIF5B is a novel interacting partner of BNIP-2 and promotes myogenic differentiation. KIF5B-dependent transport of BNIP-2 is essential for its promyogenic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Cells were seeded on coverslips in six‐well plates and stained for immunofluorescence detection using confocal fluorescence microscopy as previously described . Filamentous actin was detected by rhodamine‐phalloidin (Molecular Probes) and Collagen I was detected by anti‐Collagen I (abcam, Cambridge, MA) followed by Alexa Fluor 488‐conjugated goat anti‐mouse IgG (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded on coverslips in six‐well plates and stained for immunofluorescence detection using confocal fluorescence microscopy as previously described . Filamentous actin was detected by rhodamine‐phalloidin (Molecular Probes) and Collagen I was detected by anti‐Collagen I (abcam, Cambridge, MA) followed by Alexa Fluor 488‐conjugated goat anti‐mouse IgG (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…The secreted ACh promotes neuritogensis by activating ERK through muscarinic receptors and elicits postsynaptic neurotransmission. et al, 2015) and kinesin heavy chain (Yi et al, 2015). During muscle development, BNIP-2 functions as a scaffold that links Cdo receptor for the activation of Cdc42.…”
Section: Functional Specificity Of Bch Domain Family Proteinsmentioning
confidence: 99%
“…Together with another scaffold, JLP, it leads to p38 activation at cell membrane (Kang et al, 2008). Kinesin-1 is proposed to regulate this process by anterogradely transporting BNIP-2 to cell membrane to allow it to interact with Cdo receptor for p38 activation (Yi et al, 2015). Unlike the properties of BNIP-H, BNIP-2 fails to recognize ACL and does not regulate cholinergic signaling for neurite outgrowth.…”
Section: Functional Specificity Of Bch Domain Family Proteinsmentioning
confidence: 99%
“…Besides phosphorylation, additional regulatory mechanisms were found to control p38MAPK signaling. Our previous findings revealed that the spatial regulation of this signaling complex is dependent on KIF5B-dependent anterograde transport (19). In addition, the stability of p38MAPK is regulated by association with MAPK-activated protein kinase 2 (MK2) or MAPK-activated protein kinase 3 (MK3).…”
mentioning
confidence: 99%